Local development applied to the energy scheme using the geographic information system for decision making - María Rodríguez Gámez; Antonio Vázquez Pérez; Mirelys Torres Pérez; José R. Núñez Alvarez (Institute of Advanced Engineering and Science, 2022)
The availability of endogenous energy resources in the province of Manabí can play an important role in achieving a diverse and sustainable territorial energy matrix. This research work shows the results of the project called geographic information system for sustainable development through the use of renewable energy sources. For the management of the project database, the geographic information system was used, and the information analysis took into account the works published in the main international databases on the use of renewable sources, planning energy, decision-making, and local development. The work allows revealing the energy potential that the territory of Manabí has in terms of the availability of renewable energy sources using the geographic information system, which can help in the decision-making process that contributes to the achievement of a diverse and sustainable territorial energy matrix.